Investigating Washback of National Standardized School Examination on Junior High School Students and Teachers - Sumpada, Alief Imani (Department of English Language and Literature, Faculty of Languages and Arts, 2019)
This final project aimed to investigate the washback of English National Standardized School Examination on Ninth Graders and Teachers. The research used descriptive qualitative method as its research methodology. The results showed that English National Standardized School Examination or Ujian Sekolah Berstandar Nasional (USBN) brought positive and negative effect. The students applied some learning strategies to develop their reading and writing skills to face English USBN. However, they gave less attention to listening and speaking skills. Also, the students focused to get good result on the examination because it determined their graduation and their higher level school. The teachers prepare the students to take the examination by taught the material more thoroughly. They used various sources and media to support the teaching and learning activities. However, they gave less attention on listening and speaking skills and lose instructional time. To summarize, there were trends of positive and negative washback of English USBN on the students and teacher at SMP N 1 Kertek in academic year of 2018/2019.